2019
DOI: 10.3389/fpsyt.2019.00640
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety-Related Coping Styles, Social Support, and Internet Use Disorder

Abstract: Objective: The Internet can offer a seemingly safe haven for those being disappointed by relationships in the “offline world”. Although the Internet can provide lonely people with opportunities to seek for help and support online, complete withdrawal from the offline world comes with costs. It is discussed if people can even become “addicted” to the Internet. Of note, meanwhile, many researchers prefer the term Internet use disorder (IUD) instead of using the term “Internet addiction”. To illustrate the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 125 publications
4
8
1
1
Order By: Relevance
“…This finding is consistent with previous research on relations between AS and PSU (Elhai, Levine, O'Brien, & Armour, 2018 ), relations between AS with PIU (Seyed Hashemi et al, 2020 ), and is consistent with theory on AS (see Taylor, 2014 for a review). It fits also with earlier findings by Jung et al ( 2019 ) showing that a vigilant coping style is related to PIU, although that paper did not investigate depression/anxiety. Specifically, smartphones may offer a convenient, socially acceptable source of avoidance and distraction from anxiety symptoms during times of stress and distress.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous research on relations between AS and PSU (Elhai, Levine, O'Brien, & Armour, 2018 ), relations between AS with PIU (Seyed Hashemi et al, 2020 ), and is consistent with theory on AS (see Taylor, 2014 for a review). It fits also with earlier findings by Jung et al ( 2019 ) showing that a vigilant coping style is related to PIU, although that paper did not investigate depression/anxiety. Specifically, smartphones may offer a convenient, socially acceptable source of avoidance and distraction from anxiety symptoms during times of stress and distress.…”
Section: Discussionsupporting
confidence: 91%
“…In the context of the present work, different coping styles investigated within repressor/sensitizer theory are relevant. Vigilance coping (hence those persons more sensitive toward danger and likely more anxiety sensitive) was also associated with PIU (Jung et al, 2019 ). Because being focused upon AS leads to fear/avoidance of physical sensations, AS may influence the relationship between anxiety with PSU by driving smartphone engagement during times of stress and distress.…”
Section: Introductionmentioning
confidence: 99%
“…With each additional point of social support, the probability of male freshmen being assigned to the moderate-risk group and the high-risk group decreased by 3.5 and 7.6%, respectively. The results are in conformity with the extant literature that studied the relationship between social support and internet addiction ( 76 78 ). Study showed that participants with higher scores in receiving social support reported the lowest tendencies toward internet use disorder ( 76 ).…”
Section: Discussionsupporting
confidence: 89%
“…The results are in conformity with the extant literature that studied the relationship between social support and internet addiction ( 76 78 ). Study showed that participants with higher scores in receiving social support reported the lowest tendencies toward internet use disorder ( 76 ). Obviously, social support is a potential factor for internet addiction ( 77 , 78 ).…”
Section: Discussionsupporting
confidence: 89%
“…This result specifies the understanding of the financial award's effect on their cognitive trait anxiety and selected coping skills. The results of our research extend the knowledge of previous researches showing that anxiety is closely related to skills to manage stress (Rahnama et al, 2017;Jung et al, 2019;Kaplánová, 2019a,c;Morales-Rodríguez and Pérez-Mármol, 2019).…”
Section: Discussionsupporting
confidence: 88%